1971
DOI: 10.1042/cs0410063
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Reflexes in Parkinsonism

Abstract: 1. Cardiovascular reflex activity has been studied in thirty Parkinsonian patients, none of who had received levodopa or sympatholytic drugs.2. Changes in blood pressure and pulse rate in response to Valsalva's manoeuvre and head-up tilt were investigated by intra-arterial recording.3. Cardiovascular reflexfunction deteriorated with advancing age, but there was no correlation with either the duration or the severity of the Parkinsonism.4. These results are discussed in relation to previous reports of hypotensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1
2

Year Published

1972
1972
2003
2003

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 7 publications
0
9
1
2
Order By: Relevance
“…Our results agree very well with these earlier findings but disagree with both those of Aminoff and Wilcox [7], who have reported intact cardio vascular reflexes in their series of 11 patients with PD, and with those of Reid et al [8] and Gross et al [4], who did not find any differ ence in the pulse rate as a response to the Valsalva manoeuvre. This discrepancy is possibly at least partially due to the dissimi lar or differently selected clinical patients.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Our results agree very well with these earlier findings but disagree with both those of Aminoff and Wilcox [7], who have reported intact cardio vascular reflexes in their series of 11 patients with PD, and with those of Reid et al [8] and Gross et al [4], who did not find any differ ence in the pulse rate as a response to the Valsalva manoeuvre. This discrepancy is possibly at least partially due to the dissimi lar or differently selected clinical patients.…”
Section: Discussioncontrasting
confidence: 54%
“…Conflicting results have been reported in earlier studies concerning cardiovascular re flexes in PD [2,4,[7][8][9]. Because the results of these studies are based on a small number of patients, the present study was under taken firstly to obtain further information on the occurrence and severity of the ANS fail ure in PD by using cardiovascular reflexes and secondly to ascertain the clinical corre lates of these abnormalities.…”
Section: Introductionmentioning
confidence: 69%
“…Through this line arterial blood pressure was monitored with a transducer (Bell & Howell) and, by differentiating the signal electrically, axillary artery dP/dt was derived and was used as a measure of cardiac contractility. The evidence that this parameter gives a measure of cardiac contractility is derived from observations in normal man, Parkinsonian patients (Reid, Calne, George, Pallis & Vakil, 1971;Reid, Calne, George & Vakil, 1972) and anaesthetized dog and is as follows: (a) The increase in dP/dt after i.v. isoprenaline and stellate ganglion stimulation is specifically and reversibly antagonized by ,3-adrenoceptor blockade ( Figure 2).…”
Section: Methodsmentioning
confidence: 99%
“…Meco et al [87] reported a reduced Valsalva ratio in PD patients before and after therapy, but the difference was significant compared with control groups before therapy only. Additional studies reported changes in the Valsalva reflex in parkinsonian patients [13,59], although these differences were not confirmed in other reports [89]. The discrepancies between study results may be because of variations in patient selection, study design, and choice of control groups.…”
Section: Orthostatic Hypotensionmentioning
confidence: 89%